2020
DOI: 10.1038/s41389-020-0198-z
|View full text |Cite
|
Sign up to set email alerts
|

MFAP2 is overexpressed in gastric cancer and promotes motility via the MFAP2/integrin α5β1/FAK/ERK pathway

Abstract: Gastric cancer (GC) is one of the most common malignancies and its prognosis is extremely poor. This study identifies a novel oncogene, microfibrillar-associated protein 2 (MFAP2) in GC. With integrative reanalysis of transcriptomic data, we found MFAP2 as a GC prognosis-related gene. And the aberrant expression of MFAP2 was explored in GC samples. Subsequent experiments indicated that silencing and exogenous MFAP2 could affect motility of cancer cells. The inhibition of silencing MFAP2 could be rescued by ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 98 publications
5
39
0
Order By: Relevance
“…DLK1, a noncanonical Notch ligand, has a demonstrated role in promoting ovarian carcinogenesis via Notch activation and epithelial-mesenchymal transition [24]. The microfibrillar-associated protein 2 (MFAP2), previously named microfibril-associated glycoprotein 1 (MAGP1), activates integrin signaling and is a potential oncogene [25][26][27]. Another protein identified at FDR < 0.05, Netrin-G1 or NTNG1, is involved in apoptosis and known to be dysregulated particularly in endocrine-related tumors [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…DLK1, a noncanonical Notch ligand, has a demonstrated role in promoting ovarian carcinogenesis via Notch activation and epithelial-mesenchymal transition [24]. The microfibrillar-associated protein 2 (MFAP2), previously named microfibril-associated glycoprotein 1 (MAGP1), activates integrin signaling and is a potential oncogene [25][26][27]. Another protein identified at FDR < 0.05, Netrin-G1 or NTNG1, is involved in apoptosis and known to be dysregulated particularly in endocrine-related tumors [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…13 Li et al found that MFAP2 was up-regulated in gastric cancer and promotes motility of cancer cells through MFAP2/ integrin alpha 5 beta 1/FAK/ERK pathway. 14 Wang et al also reported that MFAP2 could promote epithelialmesenchymal transition process of gastric cancer by activating TGF-beta/SMAD2/3 pathway. 15 However, whether MFAP2 has an essential role in promoting PTC progression has not been studied yet.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown that the gene that codes MFAP2 is located at 1p36.13, and is associated with several malignant tumor types ( 6 , 7 ). Consequently, MFAP2 is upregulated in breast cancer ( 8 ), thyroid cancer ( 9 ), melanoma ( 10 ), ovarian cancer ( 11 ) and gastric cancer ( 12 , 13 ), and associated with the occurrence and progression of these tumors. Previous studies have also shown that MFAP2 is upregulated in HCC ( 14 ), but its role in the occurrence and development of the disease is unclear.…”
Section: Introductionmentioning
confidence: 99%